Exploring the relationship between employees' CSR perceptions and intention to emigrate: Evidence from a developing country. (13th June 2020) - Grabner‐Kräuter, Sonja; Breitenecker, Robert J.; Tafolli, Festim
Abstract: This study contributes to the burgeoning research on corporate social responsibility (CSR) at the individual level of analysis, in a hitherto largely neglected developing country context. Using survey information collected from 297 employees in public and private enterprises in Kosovo, this study examines how and to what extent employees' perceptions of their employer's CSR activities are associated with their intention to emigrate. Applying a needs‐based framework, this research provides evidence that employees' perceptions of CSR are positively related to the meaningfulness of their work and job satisfaction and negatively related to intention to emigrate. Additionally, results confirm that the association between CSR perceptions and emigration intention is mediated by the meaningfulness of work and job satisfaction. From a practical point of view, this research should encourage private and public enterprises in developing countries to enhance and extend their CSR engagement.